Hierarchical nanostructured polyaniline functionalized graphene/poly(vinylidene fluoride) composites for improved dielectric performances. (26th October 2016) - Maity, Nirmal; Mandal, Amit; Nandi, Arun K.
Abstract: Hierarchical nanostructured polymeric dielectric composites (PGP) based on semicrystalline poly (vinylidene fluoride) (PVDF) matrix are fabricated by incorporating polyaniline-grafted-graphene oxide (G- graft -PANI). HR-TEM images show uniform dispersion of GO within PVDF matrix. FE-SEM micrographs of PGP composites indicate fibrillar morphology produced from supramolecular organization of G- graft -PANI with PVDF chains resulting hierarchical nanostructure. The dipolar interaction between the filler and PVDF is established from FTIR spectra and Raman spectroscopy indicates reduction of GO during fabrication process. The interaction ability and high surface area of G- graft -PANI cause nonpolar α-phase PVDF to polar β-phase transformation to 91% for 5 wt% filler. PGP composites show higher melting and crystallization temperatures. It exhibit spectacular increase of dielectric permittivity, dielectric loss, and dc-conductivity relative to that of neat PVDF films. The values of dielectric permittivity and dielectric loss are 264 and 1.125 at 10 2 Hz frequency and dc-conductivity increases 8 orders from that of pristine PVDF for loading of 5% G- graft -PANI. Graphical abstract: Highlights: Reinforced PVDF composite with covalently grafted polyaniline from graphene oxide. Synergistic effect of G-graft-PANI/PVDF cause good dispersion producing ß-PVDF. Sharp increase of dielectric properties with increasing amount of G-graft-PANI. Correlation between β-phase and dielectric permittivity exhibits curve-linear plot.